Genetic bases for the metabolism of the DMS precursor S-methylmethionine by Saccharomyces cerevisiae. (September 2022) - Eder, Matthias; Sanchez, Isabelle; Camarasa, Carole; Daran, Jean-Marc; Legras, Jean-Luc; Dequin, Sylvie
Abstract: Dimethyl sulfide (DMS) is a sulfur containing volatile that enhances general fruity aroma and imparts aromatic notes in wine. The most important precursor of DMS is S- methylmethionine (SMM), which is synthesized by grapes and can be metabolized by the yeast S. cerevisiae during wine fermentation. Precursor molecules left after fermentation are chemically converted to DMS during wine maturation, meaning that wine DMS levels are determined by the amount of remaining precursors at bottling. To elucidate SMM metabolism in yeast we performed quantitative trait locus (QTL) mapping using a population of 130 F2-segregants obtained from a cross between two wine yeast strains, and we detected one major QTL explaining almost 30% of trait variation. Within the QTL, gene YLL058W and SMM transporter gene MMP1 were found to influence SMM metabolism, from which MMP1 has the bigger impact. We identified and characterized a variant coding for a truncated transporter with superior SMM preserving attributes. A population analysis with 85 yeast strains from different origins revealed a significant association of the variant to flor strains and minor occurrence in cheese and wine strains. These results will help selecting and improving S. cerevisiae strains for the production of wine and other fermented foods containing DMS such as cheese or beer. Highlights: Detection of a new allele with superior preservation of S-methylmethionine (SMM). High affinity SMM transporter gene MMP1 is the strongest phenotypic contributor. Single nucleotide polymorphism causing an early STOP codon in MMP1 is decisive. Variant mostly found in flor yeasts used for the production of characterful wines. CRISPR/Cas9 mediated base pair exchange in MMP1 resulted in better SMM.